The Effect of Work Environment, Compensation, and Career Development on Employee Job Satisfaction of PT Semen Indonesia Logistics - Nur Chamidah; Suwarno, Suwarno (Indonesian Vocational Research Journal, 2025)
PT Semen Indonesia Logistik, an affiliate of PT Semen Indonesia (Persero) Tbk, distributes and manages cement, industrial goods, and other commodities. Based on Semen Indonesia Group's environmental impact, effective distribution depends on this company. The main objective of this study is to identify and investigate the link between job satisfaction and elements like compensation, career development, and working surroundings. This research results from quantitative analysis of data gathered from fifty PT Semen Indonesia Logistik personnel. Questionnaires were used to gather data; subsequently, validity and dependability were assessed to ensure the instrument's quality. We performed basic assumption tests—which include checks for normality, multicollinearity, and heteroscedasticity—to guarantee even more the usefulness of the data. Through the lens of multiple linear regression and hypothesis evaluation, we uncovered insights into how each variable functions. To further grasp their influence, we leveraged the coefficient of determination to measure the extent of impact each independent factor has on the outcome variable. Determining workers' satisfaction on the job was more influenced by pay and promotion chances than by working circumstances.